2022
DOI: 10.3389/fneur.2022.963358
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness and safety of acupuncture for chemotherapy-induced peripheral neuropathy: A systematic review and meta-analysis

Abstract: ObjectivesThis systematic review and meta-analysis aimed to evaluate the effectiveness and safety of acupuncture on chemotherapy-induced peripheral neuropathy (CIPN).MethodsWe searched for relevant randomized controlled trials (RCTs) in PubMed, Cochrane Library, and Embase databases from their inception to 1 April 2022. The Functional Assessment of Cancer Therapy/Gynecologic Oncology Group-Neurotoxicity (FACT/GOG-Ntx), Brief Pain Inventory-Short Form (BPI-SF), the European Organisation for Research and Treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…There are currently 2 systematic reviews 18,27 of neuromodulation interventions and 4 studies [80][81][82][83] of acupuncture for CIPN similar to ours. There are similarities in the results, suggesting that such therapies reduce neuropathic pain 27,83,84 and improve patient quality of life.…”
Section: Comparison Of Similar Studiesmentioning
confidence: 57%
See 1 more Smart Citation
“…There are currently 2 systematic reviews 18,27 of neuromodulation interventions and 4 studies [80][81][82][83] of acupuncture for CIPN similar to ours. There are similarities in the results, suggesting that such therapies reduce neuropathic pain 27,83,84 and improve patient quality of life.…”
Section: Comparison Of Similar Studiesmentioning
confidence: 57%
“…There are similarities in the results, suggesting that such therapies reduce neuropathic pain 27 , 83 , 84 and improve patient quality of life. 81 , 83 It can also be combined with usual care to improve outcomes. 82 However, unlike other studies: we found that neuromodulation interventions significantly improved CIPN symptoms (FACT-Ntx and EORTC QLQ-CIPN20) compared with usual care, but there was no significant difference in efficacy compared with sham stimulation across all outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, its effectiveness in improving FC and HRQOL has been verified [20,21]. Despite the limited number of randomized clinical trials examining the safety and efficacy of acupuncture in CKD patients receiving maintenance HD, these parameters have been extensively investigated and established across diverse medical conditions [28][29][30][31][32][33][34]. Nevertheless, the results of a recent review and meta-analysis indicate that acupuncture may be a safe and effective therapeutic alternative for uremic pruritus in patients undergoing HD.…”
Section: Discussionmentioning
confidence: 99%
“…Other treatment alternatives are venlafaxine, pregabalin, amitriptyline, tramadol, strong opioids and topical baclofen (87); although limited evidence and ASCO advices against use outside studies (88). A meta-analysis of acupuncture showed no improvement in CIPN symptoms or impairment, but pain was relieved (151). Treatment decisions should take depression, anxiety, and sleep into consideration due to association with CIPN (121,152).…”
Section: Prevention and Treatment Of Cipnmentioning
confidence: 99%